Immune effector cell-associated hematotoxicity: EHA/EBMT consensus grading and best practice recommendations - Rejeski, Kai Dannebom; Subklewe, Marion; Aljurf, Mahmoud; Bachy, Emmanuel; Balduzzi, Adriana; Barba, Pere; Bruno, Benedetto; Benjamin, Reuben; Carrabba, Matteo G.; Chabannon, Christian; Ciceri, Fabio; Corradini, Paolo; et al. (Blood, 2023)
Abstract - Hematological toxicity is the most common adverse event after chimeric antigen receptor (CAR) T-cell therapy. Cytopenias can be profound and long-lasting and can predispose for severe infectious complications. In a recent worldwide survey, we demonstrated that there remains considerable heterogeneity in regard to current practice patterns. Here, we sought to build consensus on the grading and management of immune effector cell-associated hematotoxicity (ICAHT) after CAR T-cell therapy. For this purpose, a joint effort between the European Society for Blood and Marrow Transplantation (EBMT) and the European Hematology Association (EHA) involved an international panel of 36 CAR T-cell experts who met in a series of virtual conferences, culminating in a 2-day meeting in Lille, France. On the basis of these deliberations, best practice recommendations were developed. For the grading of ICAHT, a classification system based on depth and duration of neutropenia was developed for early (day 0-30) and late (after day +30) cytopenia. Detailed recommendations on risk factors, available preinfusion scoring systems (eg, CAR-HEMATOTOX score), and diagnostic workup are provided. A further section focuses on identifying hemophagocytosis in the context of severe hematotoxicity. Finally, we review current evidence and provide consensus recommendations for the management of ICAHT, including growth factor support, anti-infectious prophylaxis, transfusions, autologous hematopoietic stem cell boost, and allogeneic hematopoietic cell transplantation. In conclusion, we propose ICAHT as a novel toxicity category after immune effector cell therapy, provide a framework for its grading, review literature on risk factors, and outline expert recommendations for the diagnostic workup and short- and long-term management.